VARIABILITY OF SOME BROOMRAPE POPULATIONS FROM CHINA. Genotyping and determination of genetic polymorphism (II) - Maria DUCA (Academy of Sciences of Moldova, 2021)
Genetic diversity within a population is reflected by variations in genetic material among individuals and can manifest at the phenotypic level through new characters or traits. The emergence of a large number of O. cumana races in a short period of time demonstrates that there are higher genetic variability in populations and a high ability to adapt in the face of environmental conditions. The aim of the research presented in this article was to study the intraand interpopulation genetic diversity and genetic relationships between individuals of three populations of O. cumana from different geographical regions of the People’s Republic of China based on molecular markers (ISSR and SSR). The high intrapopulation genetic variability calculated on the basis of the allelic diversity parameters and specific genetic diversity coefficients was revealed by SSR markers while as for the ISSR primers a high degree of genetic variations was found at the interpopulation level. UPGMA clustering and principal component analysis performed according to both sets of molecular markers allowed to devide all genotypes into 5 major groups for the degree of dissimilarity and level of aggression. This study is of interest in understanding the population genetic structure of the parasitic species of O. cumana from China and could contribute to the development of pathogen control durable strategies and effective sunflower breeding programs to broomrape resistance.